2020
DOI: 10.3389/fpsyt.2020.00114
|View full text |Cite
|
Sign up to set email alerts
|

Dark Times: The Role of Negative Reinforcement in Methamphetamine Addiction

Abstract: Methamphetamine use is associated with substantial adverse outcomes including poor mental and physical health, financial difficulties, and societal costs. Despite deleterious long-term consequences associated with methamphetamine, many people use drugs for short-term reduction of unpleasant physical or emotional sensations. By removing these aversive states, drug use behaviors are negatively reinforced. Abstinence from methamphetamine can then result in a return to previous aversive emotional states linked to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 111 publications
2
49
0
Order By: Relevance
“…We previously argued that negative reinforcement processes, i.e. “relief use”, the use of a substance to prevent the occurrence of an aversive future state, is central to the maintenance of the use disorder and is modulated by ( Kohno et al., 2019 ) internal body sensations ( Wang and Roy, 2017 ), aversive interoception, and ( Hofford et al., 2019 ) conditioned stimuli that are associated with heightened negative emotions, drug craving, withdrawal, or stress ( May et al., 2020 ). As part of the T-1000 project assessments, we modified the Customary Drinking and Drug Use Record (CDDR) to include the Michigan Negative Reinforcement Questionnaire (MNRQ) to evaluate subject beliefs concerning the positive and negative consequences of the subject's drug use in reference to their primary drug of abuse.…”
Section: Resultsmentioning
confidence: 99%
“…We previously argued that negative reinforcement processes, i.e. “relief use”, the use of a substance to prevent the occurrence of an aversive future state, is central to the maintenance of the use disorder and is modulated by ( Kohno et al., 2019 ) internal body sensations ( Wang and Roy, 2017 ), aversive interoception, and ( Hofford et al., 2019 ) conditioned stimuli that are associated with heightened negative emotions, drug craving, withdrawal, or stress ( May et al., 2020 ). As part of the T-1000 project assessments, we modified the Customary Drinking and Drug Use Record (CDDR) to include the Michigan Negative Reinforcement Questionnaire (MNRQ) to evaluate subject beliefs concerning the positive and negative consequences of the subject's drug use in reference to their primary drug of abuse.…”
Section: Resultsmentioning
confidence: 99%
“…Negative reinforcement is one of the two important theories of drug dependency ( 14 ). It focuses on emphasizing that, after the drug use, the current bad mood that the addicts are suffering from gets relieved or disappears and that the appearance of negative emotions motivates and maintains the addicts' seeking behavior to continue using the drugs ( 15 ). Past studies have shown that, during the COVID-19 outbreak, the incidence and severity of anxiety and depression in the general population generally increases ( 16 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, in the case of cyber security behaviours, the reward is that nothing bad will happen; that is, the user's computer system will not be attacked if they comply with security policies. In other words, complying with cyber security behaviours is an example of negative reinforcement in which actions (i.e., complying with cyber security policies) prevent the occurrence of a negative outcome (Sidman, 2006;May et al, 2020).…”
Section: Improving Security Behaviours Using Psychological Methodsmentioning
confidence: 99%